Diabetes in childhood cancer survivors: emerging concepts in pathophysiology and future directions - Bhandari, Rusha; Armenian, Saro H.; McCormack, Shana; Natarajan, Rama; Mostoufi-Moab, Sogol (Frontiers in Medicine, 2023)
With advancements in cancer treatment and supportive care, there is a growing population of childhood cancer survivors who experience a substantial burden of comorbidities related to having received cancer treatment at a young age. Despite an overall reduction in the incidence of most chronic health conditions in childhood cancer survivors over the past several decades, the cumulative incidence of certain late effects, in particular diabetes mellitus (DM), has increased. The implications are significant, because DM is a key risk factor for cardiovascular disease, a leading cause of premature death in childhood cancer survivors. The underlying pathophysiology of DM in cancer survivors is multifactorial. DM develops at younger ages in survivors compared to controls, which may reflect an “accelerated aging” phenotype in these individuals. The treatment-related exposures (i.e., chemotherapy, radiation) that increase risk for DM in childhood cancer survivors may be more than additive with established DM risk factors (e.g., older age, obesity, race, and ethnicity). Emerging research also points to parallels in cellular processes implicated in aging- and cancer treatment-related DM. Still, there remains marked inter-individual variability regarding risk of DM that is not explained by demographic and therapeutic risk factors alone. Recent studies have highlighted the role of germline genetic risk factors and epigenetic modifications that are associated with risk of DM in both the general and oncology populations. This review summarizes our current understanding of recognized risk factors for DM in childhood cancer survivors to help inform targeted approaches for disease screening, prevention, and treatment. Furthermore, it highlights the existing scientific gaps in understanding the relative contributions of individual therapeutic exposures and the mechanisms by which they exert their effects that uniquely predispose this population to DM following cancer treatment.